2015
DOI: 10.1117/1.jmm.14.1.013507
|View full text |Cite
|
Sign up to set email alerts
|

Broader view on extreme ultraviolet masks: adding complementary imaging modes to the SHARP microscope

Abstract: Abstract. The authors are expanding the capabilities of the SHARP microscope by implementing complementary imaging modes. SHARP (the SEMATECH High-NA Actinic Reticle Review Project) is an actinic, synchrotron-based microscope dedicated to extreme ultraviolet photomask research. SHARP's programmable Fourier synthesis illuminator and its use of Fresnel zoneplate lenses as imaging optics provide a versatile framework, facilitating the implementation of diverse modes beyond conventional imaging. In addition to SHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…It is true that using OAI imaging helps to increase the resolution in 1D but introduces aberration and sideband artifacts, which effectively lower the resolution in the 2D image. This aspect has also been reported in OAI lithography (Benk et al, 2015). As a result, in the middle of the FOV (within a diameter of $200 mm = half the diameter of zone plate), the resolution of the system is reasonable (in the range 200-300 nm) and determined by the effective pixel size (because Áp > Ár), but gradually decreases in the outer part.…”
Section: Proof Of Conceptsupporting
confidence: 71%
“…It is true that using OAI imaging helps to increase the resolution in 1D but introduces aberration and sideband artifacts, which effectively lower the resolution in the 2D image. This aspect has also been reported in OAI lithography (Benk et al, 2015). As a result, in the middle of the FOV (within a diameter of $200 mm = half the diameter of zone plate), the resolution of the system is reasonable (in the range 200-300 nm) and determined by the effective pixel size (because Áp > Ár), but gradually decreases in the outer part.…”
Section: Proof Of Conceptsupporting
confidence: 71%
“…The ability of XCT to nondestructively produce tomographic images of silicon-based samples with nanometer axial resolution holds promise for applications in the growing sector of semiconductor metrology. Especially, the investigation of lithographic masks could be a promising application 25 . We expect that XCT can become a widely applied microscopy technique, in particular when more prevalent XUV sources like high harmonic generation in gases 9 10 or radiation from laser plasmas 26 27 are used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that the quality of the OV beams formed by an SFZP decreases as the focal length modulus increases at a fixed waist radius of the illuminating beam [149]. Nevertheless, the unique properties of SFZPs allow them to be used in various applications, such as detection of wavefront helicity [150,151], optical profilometry [152], the formation of vortex beams in the extreme ultraviolet range [153], optical microscopy [154], and the formation of the inverse energy flux [155]. Such elements can be used, among other things, to create stable `rainbow' OV beams in white light that persist at sufficiently large distances (up to 80 m for a beam diameter of several millimeters), which is important for solving various fundamental and applied scientific problems [146].…”
Section: Spiral Fresnel Zone Platesmentioning
confidence: 99%
“…To fabricate SFZPs, approaches similar to those used to fabricate fork-shaped holograms and gratings can be used: lithography and liquid etching methods [160,170], LCSLMs [149], projection lithography [171], direct laser recording methods [162,163,172,173] (Fig. 5b, c), laser printing [174], electron beam lithography [152,154,158], and element template transfer using an electronic exposure device [165]. An interesting option for fabricating SFZPs on the surface of a zinc oxide crystal by etching was shown in [175]: such a diffractive element allows not only forming an optical beam but also performing a nonlinear frequency conversion of the initial radiation to higher-order harmonics.…”
Section: Spiral Fresnel Zone Platesmentioning
confidence: 99%